Development of an Applied Visual Arts Learning Model Based on Local Natural Potential to Enhance Students’ Creativity at SMA 3 Pangkep - Sri Darmawanti; Andi Taslim Saputra (LPPM Institut Seni Indonesia Padangpanjang, 2026)
This study aims to develop an applied visual arts learning model based on the use of local natural potential to enhance senior high school students’ creativity. The research employed a Research and Development approach by adapting the 4D model, which consists of defining, designing, developing, and disseminating stages. The trial subjects were 30 twelfth-grade students of SMAN 3 Pangkep in the 2022/2023 academic year. Data were collected through expert and practitioner validation, student activity observation, student and teacher response questionnaires, assessment of the teacher’s ability to manage learning, and creativity-based learning achievement tests. The findings indicate that the developed model and its learning devices were categorized as highly valid based on expert judgment. The classroom trial also showed that the model was practical, as almost all learning components were implemented according to the planned procedures. Furthermore, the model was effective because classical learning mastery was achieved, student activities met the expected criteria, the teacher’s ability to manage learning was categorized as very good, and both student and teacher responses were positive. Therefore, the applied visual arts learning model based on local natural potential can serve as an alternative learning strategy in arts education, encouraging material exploration, creative practice, and contextual creativity development.